LAPAROSTOMY IN EMERGENCY SURGERY - Лещишин, Ярослав Миронович; Баранов, Андрей Игоревич; Потехин, Константин Владимирович; Мартынов, Александр Анатольевич; Ярощук, Сергей Александрович (Medicine in Kuzbass, 2019)
Laparostomy, as a technical method of completing the surgical manual has been used by surgeons for a long time. The most common indication is a common purulent peritonitisAim – evaluation of the effectiveness of laparostomy and planned sanitation as a method of treatment of common purulent peritonitis.Materials and methods. A retrospective study of the use of planned sanitation and laparostomy, for the period from 2013 to 2015, in patients with widespread purulent peritonitis, its effectiveness. Evaluation criteria - mortality and the presence of postoperative complications diagnosed in the hospital. Inclusion criteria: patients with advanced purulent peritonitis in primary surgery requiring laparotomy. Exclusion criteria: severe immune disorders, CRF; pancreonecrosis; liver cirrhosis class C; carcinomatosis, cancer cachexia; disseminated tuberculosis; total mesenteric thrombosis.Results. During this period, 101 medical records were selected. 48 men (47.5 %) and 53 women (52.5 %) each. The median age is 63.The whole group is divided into three subgroups according to the severity of peritonitis according to MPI: I st. – 20; II st. – 57; III st. – 24. In the first subgroup of UPS – Me – 10; in the second – 10; in the third – 13. Routine sanitation of the abdominal cavity in combination with the imposition laparostomy used in 34 cases (of 33.6 %). In the first subgroup twice (10 %), in the second subgroup – 18 (31.6 %), in the third – 14 (58.3 %). Number of dead – 32 (31.6 %). In each subgroup, mortality was respectively – 0; 17 (29.8 %); 15 (62.5 %).The number of complications: surface IHV – 3 (2.9 %), deep IHV – 12 (11.9 %), iohw body/hollow – 1 (0.9 %), dehiscence of anastomosis – 1 (0.9 %); eventtrace – 3 (2.9 %) and seroma postoperative wounds – 2 (1.9 %), hematoma postoperative wound – 1 (0.9 %). Other complications in 12 cases (11.9 %): pneumonia – 8 (7.9 %), thromboembolic complications in 2 (1.9 %), acute cerebrovascular accident – 1 (0.9 %), acute renal failure – 1 (0.9 %).Conclusion. The most effective method in patients of middle age 40-50 years. compensated pathology, without obvious organ failure, II st. severity of peritonitis by MPI , with abdominal index 13-16 B. The optimal number of sanations is not more than two. Patients of elderly and senile age with decompensated concomitant diseases, severe multiple organ failure and III st. the severity of peritonitis according to MPI requires a revision of surgical management tactics, in the direction of reducing the degree of surgical aggression.
Keywords: common purulent peritonitis; laparostoma; planned sanitation; Mannheim peritonitis index